From Gumball to Glitch Art: images to think images (Palíndromo, 2020)
This work is part of the master’s degree research that analyzes audiovisual products consumed by Brazilian students seeking to understand these products as places of formation and as a strategic possibility of access to contemporary art. The choice of productions - one of the television media and the other a video installation - was because they both have metalanguages and question the very structure and functionality of images and representations. The methodology of analysis consisted in describing and interrelating the effects of sense provoked by these productions, trying to understand, through the interaction regime of the accident, how the nonsense style causes ruptures in the habitual mechanisms of reading from its effects of surprise and of estrangement. The conclusions point out that critically addressing audiovisual productions consumed daily by students has become one of the contemporary challenges of art education.
Keywords: teaching; contemporary art; Glitch Art; discursive semiotics